Beauty's Release - Anne Rice (A.N. Roquelaure)
From Anne Rice, author of Beauty's Kingdom, the third book in the erotic Sleeping Beauty seriesBefore E.L. James' Fifty Shades of Grey and Sylvia Day's Bared to You,, there was Anne Rice$1 (Bs provocative take on the timeless fairy tale (3z(BSleeping Beauty. (3z (BIn the final volume of Anne Rice's deliciously tantalizing erotic trilogy, Beauty's adventures on the dark side of sexuality make her the bound captive of an Eastern Sultan and a prisoner in the exotic confines of the harem. As this voluptuous adult fairy tale moves toward conclusion, all Beauty's encounters with the myriad variations of sexual fantasy are presented in a sensuous, rich prose that intensifies this exquisite rendition of Love's secret world, and makes the Beauty series and incomparable study of erotica. In it, Anne Rice, writing as A.N. Roquelaure, makes the forbidden side of passion a doorway into the hidden regions of the psyche and the heart.s